Writing the River - Leslie Thomas (Open Rivers, 2018)

(untitled)
What does the river say to you? This is the core question posed by Write to the River, a creative writing project that I launched in partnership with the Twin Cities nonprofit Friends of the Mississippi River and photographer Tom Reiter, in spring 2017.